In vitro antifungal activity of chitosan on Bipolaris oryzae, rice pathogen - Aida Tania Rodríguez Pedroso; Maribel Plascencia Jatomea; Silvia Bautista Baños; Mario Onofre Cortéz Rocha; Miguel Ángel Ramírez Arrebato (Acta Agronómica, 2016)
The aim of this study was to determine the effect and Media Inhibitory Concentration (MIC50), of chitosans of different molecular masses on mycelial growth, hyphal diameter, structural changes, spore germination and fungal biomass production B. oryzae. The results indicated that the average molecular mass chitosan showed higher inhibitory effect (p≤0.05); however, the low molecular weight chitosan affected more hyphal diameter at the highest concentration used (4000 mg/l) Observations of hyphae through the scanning electron microscopy (SEM) showed that the fungus treated with chitosan at the concentration of 3000 mg/l achieved a high spore production. The average molecular mass chitosan had the lowest MIC value was 2182.9 mg/l. The germination of spores treated with CMI50 was affected and biomass production of the fungus.